Mesoplastic occurrence in the sandy beaches of Cagayan de Oro City, the Philippines - Perpetua, Zy D. (Philippine Journal of Science, 2025)
Plastics have emerged as a significant threat to marine ecosystems. Numerous studies have been undertaken on macroplastics and microplastics. However, mesoplastics (5–25 mm) remain poorly studied in the Philippines. This study assessed mesoplastic pollution on three sandy beaches in Cagayan de Oro City – namely Buluacay Beach (B1), Bulua Seaside (B2), and Miramar Beach (B3). A total of 82 mesoplastics with a mean concentration of 72.30 items/m2 or 1.70 items/kg dry weight were collected and characterized by shape, color, size, and polymer type, with identification confirmed via ATR-FTIR. The highest concentration was observed at Bulua Seaside, with a mean concentration of 100.00 ± 16.50 items/m2 or 2.39 ± 0.33 items/kg dw, whereas the lowest concentration was recorded at Buluacay Beach with a mean concentration of 50.30 ± 18.30 items/m2 or 1.18 ± 0.47 items/kg dw. Statistical analysis revealed significant differences between the three sampling sites. Film-shaped mesoplastics (39.5%), white-colored plastics (47.4%), and sizes ranging from 16-20 mm (31.6%) were the most common, and polypropylene (34.2%) was the most dominant polymer. These findings provide baseline data on mesoplastic contamination in the region and highlight the need for focused monitoring and management strategies in Philippine coastal areas.